Effects of exchangeable sodium on crusting behavior of a sandy loam soil - Painuli, DK; Abrol, IP (Commonwealth Scientific and Industrial Research Organisation, 1986)
Field and greenhouse studies were conducted at the Central Soil Salinity Research Institute, Karnal, India, to evaluate the effect of exchangeable sodium (ES), amount of water applied, and evaporation and temperature conditions at drying on the crusting behaviour of a sandy loam soil. The exchangeable sodium percentage (ESP) ranged from 5.8 to 30.7 in the field and from 6 to 60 in the greenhouse studies. Soil crusting behaviour was evaluated in terms of crust strength measured by a simulated seedling emergence technique. Water was applied as natural or simulated rainfall. Crust strength increased with ESP, amount of water applied, and temperature, but decreased with increasing evaporation demand. This change in crust strength was steep above ESP 30. Although drying of the crust increased its strength, beyond a certain degree of dryness the disappearance of water films surrounding the soil particles reduced strength for low ESP soils.